A Martini coarse-grained model of the calcein fluorescent dye. (9th August 2018) - Salassi, S; Simonelli, F; Bartocci, A; Rossi, G
Abstract: Calcein leakage assays are a standard experimental set-up for probing the extent of damage induced by external agents on synthetic lipid vesicles. The fluorescence signal associated with calcein release from liposomes is the signature of vesicle disruption, transient pore formation or vesicle fusion. This type of assay is widely used to test the membrane disruptive effect of biological macromolecules, such as proteins, antimicrobial peptides and RNA and is also used on synthetic nanoparticles with a polymer, metal or oxide core. Little is known about the effect that calcein and other fluorescent dyes may have on the properties of lipid bilayers, potentially altering their structure and permeability. Here we develop a coarse-grained model of calcein that is compatible with the Martini force field for lipids. We validate the model by comparing its dimerization free energy, aggregation behavior at different concentrations and interaction with a 1-palmitoyl-2-oleoyl- sn -glycero-3-phosphocholine (POPC) membrane to those obtained at atomistic resolution. Our coarse-grained description of calcein makes it suitable for the simulation of large calcein-filled liposomes and of their interactions with external agents, allowing for a direct comparison between simulations and experimental liposome leakage assays.